Analyzing the nonlinear pricing strategy of Cibo using an adverse selection game theory model - Lim, Dickson A. (Animo Repository, 2012)
With the inability of Cibo to correctly identify their patrons of which segment or type they are, a nonlinear pricing scheme was developed by the restaurant in the form the La Familia option. The La Familia option is a price discrimination strategy that attempts to extract surplus from either segment or type; but due to adverse selection, the product offering exhibits distortion to one of the segment or type. © 2012 De La Salle University, Philippines.